UNDERSTANDING THE MEANING OF LANGUAGE BIAS IN TWITTER STATUS - Agung Suhadi (Premise: Journal of English Education and Applied Linguistics, 2019)
Through social networking sites, many users or writers convey the strict message and statement in the platform of their twitter for whom those are addressed. This study was to analyze the use of language bias in worldwide twitter status; how its form and what is the underlying motive behind the words used. The researcher only focused on the “Trending Topic” from worldwide twitter status during February 2018 by taking up 25 twitter status as samples. The result of analysis obtained that there were six categories of language bias which are used in twitter statuses such as age, sex (gender), race, social class, and traits. Semiotically, all above upon deliver were visible strictly words, but all of the words subtle conveyed some important values for readers in terms of five categories above like to be an independent person, respect and not underestimate others. In short, by understanding the clues words of language bias in social media, readers can understand easily for whom the message or statement are addressed and not easy to give a negative response as users of social media.